Winning Strategies By Female Legislative Candidates in The 2024 General Elections in Ciamis Regency - Ida Parida; Erlan Suwarlan; Arie Budiawan (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study analyzes the winning strategies of female legislative candidates in the 2024 election in Ciamis Regency using a qualitative approach through in-depth interviews with six informants, including legislative candidates, party cadres, and political observers. The results show that the winning strategies integrate three main capitals according to Ronald S. Burt's (1995) theory: financial, human, and social capital. Despite facing limited funds, female candidates are able to optimize resources through efficient fund management, increased leadership capacity, and strengthened community-based social networks. This pattern of integrating these three capitals effectively overcomes structural barriers such as patriarchal culture and limited political access. This study confirms the relevance of Burt's three capitals theory in the context of local Indonesian politics, adapting to digital dynamics. Its practical implications emphasize the importance of holistic women's political cadre development and alternative funding policies based on crowdfunding.